Muscarinic cannabinoid suppression of excitation, a novel form of coincidence detection - Michaela Dvorakova; Ken Mackie; Alex Straiker (Pharmacological Research)
Δ9-tetrahydrocannabinol (THC), the chief psychoactive ingredient of cannabis, acts in the brain primarily via cannabinoid CB1 receptors. These receptors are implicated in several forms of synaptic plasticity – depolarization-induced suppression of excitation (DSE), metabotropic suppression of excitation (MSE), long term depression (LTD) and activation-dependent desensitization. Cultured autaptic hippocampal neurons express all of these, illustrating the rich functional and temporal heterogeneity of CB1 at a single set of synapses. Here we report that coincident activation of muscarinic acetylcholine receptors and elicitation of DSE in autaptic hippocampal neurons results in a substantial (∼40 %) and temporally precise inhibition of excitatory transmission lasting ∼10 minutes. Its induction is blocked by CB1 and muscarinic M3/M5 receptor antagonists and is absent in CB1 receptor knockout neurons. Notably, once it is established, inhibition is reversed by a CB1, but not a muscarinic, antagonist, suggesting that the inhibition occurs via persistent activation of CB1 receptors. We refer to this inhibition as muscarinic cannabinoid suppression of excitation (MCSE). MCSE can be mimicked by coapplication of muscarinic and cannabinoid agonists and requires Ca2+-release from internal stores. As such, MCSE represents a novel and targeted form of coincidence detection – important for many modes of learning and memory -- between cannabinoid and muscarinic signaling systems that elicits a medium-duration depression of synaptic signaling. Given the known roles of muscarinic and cannabinoid receptors in the hippocampus, MCSE may be important in the modulation of hippocampal signaling at the site of septal inputs, with potential implications for learning and memory, epilepsy and addiction.